Analysis And Design Of Online Based Plastic Sales Information System With User Acceptance Testing Method - Ronal Yap_ronal; Rudy Arijanto (bit-Tech, 2023)
The purpose of this research is to design applications that can be directly used by customers to help speed up the selectionof plastic products according to the criteria and desires of customers and to expand the sales area of plastic shops thathave not been reached. The method used in this study is UAT is one of the most innovative methodologies to preventIT project failure. The UAT process begins by providing documentation of business requirements, then continues withbusiness processes (workflows) or scenarios and finally tests using data. Effectiveness in testing is needed in thedevelopment of an application or information system so that the product can arrive at the user on time and according tothe user's needs. Tests carried out on the built system are divided into two mechanism tests, namely alpha testing usingthe black box method and beta testing using a Likert scale. The results obtained from this research are that this ecommerce website can be used directly by customers to help speed up the selection of rice products according to thecriteria and wishes of customers, this online sales website is also very helpful in marketing plastic products in a wide areacoverage and test results with user acceptance testing getting an average result of 94.67% it can be concluded that ECommerce is made for UD customers. Various Plastics are in accordance with user needs.